Mitigating Internet bottleneck with fractional temporal evolution of optical solitons having quadratic–cubic nonlinearity - Rezazadeh, Hadi; Osman, Mohamed S.; Eslami, Mostafa; Ekici, Mehmet; Sonmezoglu, Abdullah; Asma, Mir; Othman, Wan Ainun Mior; Wong, B.R.; Mirzazadeh, Mohammad; Zhou, Qin; Biswas, Anjan; Belic, Milivoj (Elsevier, 2018)
This paper studies fractional temporal evolution of optical solitons with quadratic–cubic nonlinearity that comes with a few perturbation terms. Khalil's conformable fractional derivative as well as Liu's extended trial function scheme are applied to retrieve these soliton solutions. The results are applicable to mitigate Internet bottleneck that is a growing problem in telecommunications industry.